Complete resection of the superficial femoral artery and superficial femoral vein due to forceful trauma: a case report - Carlo Campesi; Vincenzo Molinari; Edorardo Scarcello; Francesco Intrieri (Angiologia e Cirurgia Vascular)
BACKGROUND: The incidence of superficial femoral artery trauma with or without involvement of superficial femoral vein, in the absence of organ injury or fractures, is rare. We present a case of superficial femoral artery and vein resection caused by high-energy blunt trauma.